UPAYA PENINGKATAN HASIL BELAJAR MATA PELAJARAN IPS TERPADU DENGAN METODE KOPERATIF TIPE STAD - Arbaiyah, Arbaiyah (Jurnal Paedagogy, 2020)
This classroom action research was held because of problems in student learning who have problems improving learning outcomes. The problem is because the learning method is not optimal so that actions are made using the cooperative method, namely the type STAD or student team achievement devision. This PTK was held in semester 1 of the 2017/2018 school year in class IX.C with material on Developed and Developing Countries. CAR is held in 2 cycles, each cycle with 4 stages, namely planning, implementing, observing and reflecting. After taking action with this method the student’s ability to understand the subject matter increased, from the initial average value of 66 in the first cycle to 79.5 in the second cycle and the level of learning completeness reached 88%. This shows the successful use of this method in the learning process.